PERKEMBANGAN KOMUNIKASI DIGITAL: DAMPAK MEDIA SOSIAL PADA INTERAKSI SOSIAL DI ERA MODERN - Abdul Wahab Syakhrani; Engelbertus Kukuh Widijatmoko (Jurnal Komunikasi, 2025)
The development of digital communication through social media has had a major impact on social interaction in the modern era. Social media allows easier and faster communication, and opens up opportunities to form a wide social network without being limited by geographical distance. However, behind these benefits, there are challenges such as a decline in the quality of face-to-face interactions, threats to privacy, and the spread of disinformation. With proper management, social media can continue to serve as a tool that enriches and strengthens social connections in this digital era